Differential Subcellular Distribution of Cytokinins: How Does Membrane Transport Fit into the Big Picture? - Nedvěd, Daniel; Hošek, Petr; Klíma, Petr; Hoyerová, Klára (International journal of molecular sciences, 2021)
Cytokinins are a class of phytohormones, signalling molecules specific to plants. They act as regulators of diverse physiological processes in complex signalling pathways. It is necessary for plants to continuously regulate cytokinin distribution among different organs, tissues, cells, and compartments. Such regulatory mechanisms include cytokinin biosynthesis, metabolic conversions and degradation, as well as cytokinin membrane transport. In our review, we aim to provide a thorough picture of the latter. We begin by summarizing cytokinin structures and physicochemical properties. Then, we revise the elementary thermodynamic and kinetic aspects of cytokinin membrane transport. Next, we review which membrane-bound carrier proteins and protein families recognize cytokinins as their substrates. Namely, we discuss the families of "equilibrative nucleoside transporters" and "purine permeases", which translocate diverse purine-related compounds, and proteins AtPUP14, AtABCG14, AtAZG1, and AtAZG2, which are specific to cytokinins. We also address long-distance cytokinin transport. Putting all these pieces together, we finally discuss cytokinin distribution as a net result of these processes, diverse in their physicochemical nature but acting together to promote plant fitness.
Keywords: homeostáza; proteiny huseníčku; Hydrophobic and Hydrophilic Interactions; Plant Shoots; Arabidopsis; hydrofobní a hydrofilní interakce; Thermodynamics; cytokinin transport; PUP14; ABCG14; výhonky rostlin; membránové transportní proteiny; Plant Roots; cytokinin hydrophobicity; signální transdukce; regulátory růstu rostlin; Homeostasis; Arabidopsis Proteins; membrane transport; Cytokinins; regulace genové exprese u rostlin; Membrane Transport Proteins; Signal Transduction; kořeny rostlin; cytokininy; termodynamika; Cell Membrane; biologický transport; kinetika; AZG2; Plant Growth Regulators; Gene Expression Regulation, Plant; buněčná membrána; AZG1; cytokinin distribution; Kinetics; Biological Transport